|
(1)
,3x-y=10 ① 2x-3y=9 ②
由①得:y=3x-10 ③,
把③代入②得:x=3,
把x=3代入③得:y=-1,
则原方程组的解为:
;x=3 y=-1
(2)
,2p-3q=13 ① -p+5=3q ②
①-②得:3p=18,
p=6,
把p=6代入②得:q=-
,1 3
则原方程组的解为:
.p=6 q=- 1 3
(3)
,3m-2n=5 ① 4m+2n=9 ②
①+②得:7m=14,
m=2,
把m=2代入②得:n=
,1 2
则原方程组的解为:
.m=2 n= 1 2
(4)
,3x+5y=25 ① 4x+3y=15 ②
①×4-②×3得:11y=55,
y=5,
把y=5代入②得:x=0,
则原方程组的解为:
.x=0 y=5
(5)
,3x-5y=7 ① 4x+2y=5 ②
①×4-②×3得:y=-
,1 2
把y=-
代入②得:x=1 2
,3 2
则原方程组的解为:
.x= 3 2 y=- 1 2
(6)
,
-x 2
=1 ①y+1 3 3x+2y=4 ②
由①变形得:3x-2y=8 ③,
②+③得:x=2,
把x=2代入②得:y=-1,
则原方程组的解为:
.x=2 y=-1
(7)
,
+m 2
=13 ①n 3
-m 3
=3 ②n 4
由①变形得:3m+2n=78 ③,
由②变形得:4m-3n=36 ④
③×3+④×2得:m=18,
把m=18代入④得:n=12,
则原方程组的解为:
;m=18 n=12
(8)
,
x+1 5
y=1 3
①2 5 0.5x-0.3y=0.2 ②
由①变形得:3x+5y=6 ③,
由②变形得:5x-3y=2 ④,
③×3+④×5得:x=
,14 17
把x=
代入③得:y=14 17
,12 17
则原方程组的解为:
.x= 14 17 y= 12 17
(9)
,
+2x-1 5
=2 ①3y-2 4
-3x+1 5
=0 ②3y+2 4
由①变形得:8x+15y=54 ③,
由②变形得:4x-5y=2 ④,
③+④×3得:x=3,
把x=3代入④得:y=2,
则原方程组的解为
.x=3 y=2
(10)
,
=y+1 4
①x+2 3 2x-3y=1 ②
由①变形得:4x-3y=-5 ③,
③-②得:x=-3,
把x=-3代入②得:y=-
,7 3
则原方程组的解为:
.x=-3 y=- 7 3